'Doing' philosophy as an approach to enhance thinking skills among undergraduate students - Abdullah, Norillah; Hashim, Rosnani (2011)
This paper discusses a study to find out whether philosophical inquiry (PI) can be used as a tool to develop critical thinking among the undergraduate students of the Faculty of Islamic Revealed Knowledge and Human Sciences (IRKHS), International Islamic University, Malaysia (IIUM). This qualitative study, involved two groups of students students with the first the PI group being taught using the Philosophical Inquiry approach, while another FCT group were taught the regular formal critical-thinking skill course. Data was collected from the students’ assignments, interviews, and also journal entries. Findings showed that students from the PI group were able to apply more critical thinking skills than students from the FCT group. It is also found that students from the PI group felt a change has occurred in their way of thinking and they became more open. Besides, students felt that PI approach helped to improve their self-confidence especially in expressing their ideas.